Brüning's austerity policies of the early 1930s intensified the economic slump and increased unemployment - Stephanie Ettmeier; Alexander Kriwoluzky (DIW Weekly Report, 2022)
May 2022 marked the 90th anniversary of the end of Heinrich Brüning's term as Reich Chancellor. To this day, the economic effects of Brüning's extreme austerity measures remain unclear. However, new data and calculations have made an initial quantification of the economic consequences of Brüning's policies possible. An analysis based on a time series model illustrates how the Weimar Republic's economy could have developed without Brüning's austerity measures. According to this model, real GDP fell by around 4.5 percent overall in the reference year 1932 and unemployment rose sharply as a result of Brüning's emergency decrees. Considering this analysis, current calls for fiscal austerity to reduce debt should be questioned.
Keywords: C32; E62; E65; N14; 330; Austerity; Fiscal policy; Germany; Great Depression; Structural vector autoregression